(untitled) (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
The advancement of digital technology has significantly impacted various aspects of education, including mathematics learning. Therefore, this study aims to analyze the use of technology-based applications as interactive solutions in mathematics education, particularly in enhancing students understanding and engagement in the digital era. The research employs a Systematic Literature Review (SLR) methodology, analyzing 50 scholarly articles published between 2019 and 2024. Literature sources were obtained from indexing platforms such as Google Scholar, DOAJ, and Scopus, focusing on articles relevant to the integration of technology in mathematics education. The findings indicate that technology-based applications, equipped with interactive features such as gamification, dynamic visualization, and real-time feedback, significantly enhance student engagement and facilitate a more effective understanding of abstract concepts. However, several key challenges in their implementation remain, including technological accessibility and teachers’ readiness to utilize these applications optimally. Based on these findings, technology-based mathematics applications hold substantial potential for further integration into the educational curriculum, with important considerations for addressing infrastructure limitations and the readiness of human resources